Sprouty2 downregulates angiogenesis during mouse skin wound healing - Wietecha, Mateusz S. (American Physiological Society, 2011)
Angiogenesis is regulated by signals received by receptor tyrosine kinases such as vascular endothelial growth factor receptors. Mammalian Sprouty (Spry) proteins are known to function by specifically antagonizing the activation of the mitogen-activated protein kinase signaling pathway by receptor tyrosine kinases, a pathway known to promote angiogenesis. To examine the role of Spry2 in the regulation of angiogenesis during wound repair, we used a model of murine dermal wound healing. Full-thickness excisional wounds (3 mm) were made on the dorsum of anesthetized adult female FVB mice. Samples were harvested at multiple time points postwounding and analyzed using real-time RT-PCR, Western blot analysis, and immunofluorescent histochemistry. Spry2 mRNA and protein levels in the wound bed increased significantly during the resolving phases of healing, coincident with the onset of vascular regression in this wound model. In another experiment, intracellular levels of Spry2 or its dominant-negative mutant (Y55F) were elevated by a topical application to the wounds of controlled-release gel containing cell permeable, transactivator of transcription-tagged Spry2, Spry2(Y55F), or green fluorescent protein (as control). Wound samples were analyzed for vascularity using CD31 immunofluorescent histochemistry as well as for total and phospho-Erk1/2 protein content. The treatment of wounds with Spry2 resulted in a significant decrease in vascularity and a reduced abundance of phospho-Erk1/2 compared with wounds treated with the green fluorescent protein control. In contrast, the wounds treated with the dominant-negative Spry2(Y55F) exhibited a moderate increase in vascularity and elevated phospho-Erk1/2 content. These results indicate that endogenous Spry2 functions to downregulate angiogenesis in the healing murine skin wound, potentially by inhibiting the mitogen-activated protein kinase signaling pathway.